2019
DOI: 10.1111/jse.12545
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Cedrela fissilis (Meliaceae) in the Brazilian Atlantic Forest reveals a complex phylogeographic history driven by Quaternary climatic fluctuations

Abstract: Quaternary climatic fluctuations have shaped the geographic distribution of lineages, potentially affecting the demography, genetic structure, and patterns of genetic diversity of extant species. Different phylogeographic scenarios have been proposed for plants in neotropical cloud forests during the Last Glacial Maximum based on paleoecological data: the dry refugia hypothesis (DRH) and the moist forest hypothesis. We specifically focus on the Brazilian Atlantic Forest (BAF) range of Cedrela fissilis (Meliace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…Apart from the larger-scale geographic analyses mentioned above, several studies on selected single modern Neotropical Meliaceae species, or their complexes, have been conducted in the past two decades. Among these are the works by Cavers et al (2003Cavers et al ( , 2013 on Cedrela odorata L., by Mangaravite et al (2019) on C. fissilis Vell., and by Scotti-Saintagne et al ( 2013) on a species complex in Carapa. Cavers et al (2003) studied populations of Cedrela odorata in Central America, phylogenetically grouped into three lineages (northern, central and southern), and spatial analysis confirming a deviation from a pattern of isolation by distance.…”
Section: Biogeographic Studies On Modern Meliaceaementioning
confidence: 99%
“…Apart from the larger-scale geographic analyses mentioned above, several studies on selected single modern Neotropical Meliaceae species, or their complexes, have been conducted in the past two decades. Among these are the works by Cavers et al (2003Cavers et al ( , 2013 on Cedrela odorata L., by Mangaravite et al (2019) on C. fissilis Vell., and by Scotti-Saintagne et al ( 2013) on a species complex in Carapa. Cavers et al (2003) studied populations of Cedrela odorata in Central America, phylogenetically grouped into three lineages (northern, central and southern), and spatial analysis confirming a deviation from a pattern of isolation by distance.…”
Section: Biogeographic Studies On Modern Meliaceaementioning
confidence: 99%
“…The satisfactory levels found for the genetic diversity of the species indicate that it has managed to keep up with the disturbances generated by its predatory exploitation and the fragmentation of natural populations, having as a positive factor the fact that they are located in CU's, which restrict selective cutting. Studies with vulnerable and threatened species, such as D. nigra, demonstrated that these species can restore their population, if there is genetic diversity, knowledge and, control over the genetic structure in the occurrence areas (Martinelli and Moraes, 2013;Souza et al, 2017;Mangaravite et al, 2019). This is even more relevant because D. nigra is an allogamous species, that is, it preferably performs cross-fertilization benefited by entomophilous pollination, consequently increasing the genetic diversity.…”
Section: Cernementioning
confidence: 99%
“…Quaternary glacial‐interglacial cycles have caused the migration of organisms and changed their spatial distribution patterns (Harrison et al, 2001; Hewitt, 2001; Liu & Manchester, 2019; Mangaravite et al, 2019). Organisms are also likely to die during these changes or to be preserved in refuges, later expanding from these refuges during the interglacial periods (Hewitt, 1996, 2001; Petit et al, 2003).…”
Section: Discussionmentioning
confidence: 99%